Curvature induction and membrane remodeling by FAM134B reticulon homology domain assist selective ER-phagy - Ramachandra M. Bhaskara (Nature Portfolio, 2019)
FAM134B/RETREG1 is a selective ER-phagy receptor that regulates the size and shape of the endoplasmic reticulum. Here authors use molecular modeling and molecular dynamics simulations to assemble a structural model for the reticulon-homology domain of FAM134B.